Relationship between social support and self-hardiness among breast cancer women in Nasiriyah, Iraq - Gossoon Juma Elywy; Mohammed Malih Radhi; Qasim Abbas Khyoosh AlEqabi (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the role of social support in predicting self-hardiness among women having breast cancer. Method: The descriptive correlational study was conducted at the Oncology Centre, Nasiriyah, Iraq, from August 3 to September 22, 2022, and comprised women receiving treatment for breast cancer. Data was collected using a questionnaire designed in the light of the Multidimensional Scale of Perceived Social Support, which was found reliable on the basis of a pilot study. Data was analysed using SPSS 20. Results: There were 150 women with mean age 50.4±11.18 years. Of them, 135(90%) were married, 113(75.3%) were unemployed, 90(60%) were living in rural areas, and 89(59.3%) had low socioeconomic status. Overall, 108(72%) patients reported they received little social support. Self-hardiness significantly differed in relation to marital status (p=0.021), place of residence (p=0.003) and income level (p=0.005). Social support positively correlated with self-hardiness (p=0 .000). Conclusion: Social support was found to be a predictor of increased self-hardiness that enhances resilience and enables patients to deal with one of the most devastating illnesses of modern times. Keywords: Cancer, Breast, Neoplasms, Counselling.